Reducing black carbon emissions from diesel vehicles in Russia: An assessment and policy recommendations. Issue 56 (February 2016) - Kholod, Nazar; Evans, Meredydd
Highlights: Russia has made significant progress in emission reductions from on-road transport. Diesel fleet upgrades remain slow and would benefit from active government involvement beyond the largest cities. Emission inspection and maintenance programs should be enforced to reduce emissions from diesel vehicles. Off-road vehicles represent an important opportunity for additional emission reductions; regulation is required to achieve these reductions. Abstract: The paper assesses options and challenges of reducing black carbon emissions from diesel vehicles in Russia. Black carbon is a product of incomplete diesel combustion and is a component of fine particulate matter. Particulate matter emissions have adverse health impacts, causing cardiopulmonary disease and lung cancer; black carbon is also a large climate forcer. Black carbon emissions from Russian diesel sources affect not only the Russian territory but also contribute to overall pollution. This paper analyzes current ecological standards for vehicles and fuel, evaluates policies for emission reductions from existing diesel vehicle fleet, and assesses Russia's attempts to encourage the use of natural gas as a vehicle fuel. Based on best practices of black carbon emission reductions, this paper provides a number of policy recommendations for Russia.